Peran Kelompok Tani terhadap Peningkatan Produksi Padi Sawah di Desa Puundombi Kecamatan Tongauna Utara Kabupaten Konawe - Edi Susilo; Sarty Syarbiah; I Made Sukratman (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
To analyze the role of farmer groups in increasing the production of paddy farming in Puundombi Village, Tongauna Utara District, Konawe Regency. The number of samples in this study was 19 people. Taken 10-15% or 20-25% or more of the population. The Farmer Group Role Assessment Score was measured using a Likert scale. Each criterion has a range as a limit, the respondent's answers to each variable can be classified, namely (1) High Category, (2) Medium Category, (1) Low Category. The role of the paddy farming group in Puundombi Village, Tongauna Utara District, obtained the results of the role of the farmer group "High" with an average of 2.60. The scores of the three indicators, namely the learning class with a score of 486 with an average of 2.56 high category, cooperation facilities with a score of 496 with an average of 2.61 high category and production units with a score of 502 with an average of 2.64 high category. The role of farmer groups is related to the income of rice farmers in Puundombi Village, Tongauna Utara District, Konawe Regency. The results of the Chi-Square calculation above show that the calculated X2 value is 4.337, which is greater than the X2 table of 3.841 (4.33> 3.841). Because the calculated X2 is greater than the X2 table, it can be concluded that there is a positive and significant relationship between the role of farmer groups in increasing the income of rice farming businesses in Puundombi Village, Tongauna Utara District, Konawe Regency.